Vegetative Propagation of Punica granatum by Stem Cuttings Using Non-Mist Propagator - Md. Alamgir Kabir; Mahamud Hasan Prince; Rezaul Karim; Saifur Rahman; K.M. Masum Billah; G.N. Tanjina Hasnat (International Journal of Agriculture System, 2017)
The present study was carried out to explore rooting performance of Punica granatum (Dalim) in Bangladesh through clonal propagation by stem cutting under 3 different doses of rooting hormone IBA (Indole Buetairic Acid) and planted in the perforated plastic tray filled with coarse sand and gravel placed in the non-mist propagator. The experiment was laid out following a Randomized Complete Block Design (RCBD) with 4 treatments and 4 replications (blocks). The treatments were T0= control, T1 = 0.2% IBA, T2 = 0.4% IBA, T3 = 0.8% IBA. The rooting ability of cuttings was significantly influenced by the application of IBA. The results showed that the highest rooting percentage (70%) and longest root length (11.75 cm) of P. granatum stem cuttings were obtained from the cuttings treated with 0.2% IBA followed by 0.4% IBA (47.5% and 7.95 cm respectively) whereas the highest root number (32) and maximum root diameter (2.7 mm) were recorded with 0.4% IBA followed by 0.8% IBA (28 and 2.47 mm respectively). Survival percentage of the cutlings (the rooted cuttings) after 3 months of transferring them into poly bags was also significantly enhanced by exogenous rooting hormone (IBA) application. The highest survival percentage (73.5%) was observed with 0.4% IBA treatment followed by 0.8% IBA (68.5%). Findings of the present study reveal that P. granatum is highly amenable for clonal propagation by stem cuttings using low-cost non-mist propagator and 0.4% IBA treatment may be recommended for mass production of quality planting stocks for the cultivation of the species in homestead agroforestry or in fruit orchards. These outcomes can assist to provide edible fruit to poor rural people of natural disaster vulnerable Bangladesh.